Uncertainty quantification in the techno-economic analysis of emission reduction technologies: a tutorial case study on CO2 mineralization - Strunge, Till; Renforth, Phil; Van der Spek, Mijndert (Frontiers in Energy Research, 2023)
The pathways toward net-zero greenhouse gas emissions by 2050 should be designed based on solid scientific evidence. Ex ante system analysis tools, such as techno-economic assessments (TEAs), are key instruments to guide decision-makers. As ex ante TEAs of CO2 mitigation technologies embody a high level of uncertainty, the informed use of uncertainty analysis becomes crucial for meaningful interpretation and communication of TEA outputs. To foster enhanced appreciation and the use of uncertainty analysis, we compare multiple uncertainty analysis methods for ex ante TEAs, using a case study on CO2 mineralization in the cement industry. We show that local sensitivity analysis tools such as one-way analysis, which are most often used by TEA practitioners, may not suffice for deriving reliable conclusions and provide guidance on how to apply global sensitivity analysis methods, such as variance-based indicators for TEAs in this field.